Directing self-assembly to grow adaptive physical structures. (2017) - Blaney, Adam; Dunn, Nick; Alexander, Jason; Richards, Daniel; Rennie, Allan; Anwar, Jamshed
Additive manufacturing technologies offer exciting opportunities to rethink the process of designing and fabricating physical structures. This paper outlines initial work that seeks to extend existing AM capabilities, creating physically adaptive structures by exploiting processes of self-assembling materials. The paper details an investigation of self-assembling structures that can respond to different conditions by adapting their physical properties over time. The process uses electrolysis of seawater to demonstrate a proof-of-concept of tuneable material structures, via crystal growth. Results demonstrate an aggregation-based multi-material system that is sensitive to changing environmental conditions. Material properties of grown structures have been analysed and illustrate that different materials can be created from an abundant base material (seawater) by manipulating environmental conditions (i.e. electrical current). It is found that turbulence is a useful property within these kinds of systems and that the physical properties of cathode scaffold structures have a significant impact in controlling material properties and resolution.